KEEFEKTIFAN MEDIA POP UP BOOK TERHADAP HASIL BELAJAR MATEMATIKA MATERI BILANGAN CACAH PADA SISWA KELAS IV SDN WONOREJO 02 - Nilam Permata Sari; Joko Sulianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Difficulty in understanding rounding material on numerical numbers, student activities in learning tend to be passive, the existence of pop up book media in the classroom but not maximized, thus causing student learning outcomes. Media in the classroom but not maximized, causing student learning outcomes to be less than optimal. Less than optimal. This type of research uses quantitative methods with Pre-experimental design with the form of one-group pretest-posttest design. Data collection techniques in this study through interviews, observations, tests, and documentation. The results showed an average pretest of 47.3 and an average posttest of 84.6 posttest average of 84.6. Completeness Individual learning is considered complete learning if it meets the Learning Completeness score of 70. Classical learning completeness is 98%. From these results it can be concluded that pop up book media is effective on learning outcomes learning outcomes in class IV SDN Wonorejo 02.